A thick wall concept for robust treatment of contacts in DEM simulation of highly polydisperse particulate systems - Alfano, Francesca O.; Iozzi, Giovanni; Di Maio, Francesco P.; Di Renzo, Alberto (Frontiers in Chemical Engineering, 2024)
Modelling particulate systems with the Discrete Element Method (DEM) is an established practice, both in the representation and analysis of natural phenomena and in scale-up and optimization of industrial processes. Since the method allows tracking individual particles, each element can possess geometrical, physical, mechanical or chemical surface properties different from those of the other particles. One example is a polydisperse particulate system, i.e. characterized by a size distribution, opposed to the idealized monodisperse case. In conventional DEM, a softer particle stiffness is commonly adopted to reduce the computational time. It might happen that artificially soft particles, when colliding against a wall boundary, exhibit such large, unrealistic overlap that they 'pass through' the wall and exit the domain. In the case of highly polydisperse systems, this often occurs when fine particles are pushed against the wall by coarse particles with masses several orders of magnitude larger. In the manuscript, a novel method is proposed, named thick wall, to allow the particles in contact with the walls to experience relatively large overlaps without ending up ejected out the domain. In particular, a careful way to calculate the particle-wall overlap and force unit vector can accommodate normal displacements larger than the maximum usually allowed, i.e. typically the particle radius, thereby preventing particles from being expelled from the domain. First, critical velocities for which single particles and pairs of fine/coarse particle escape the domain are analytically characterized using the linear and the Hertz models. The thick wall concept is then introduced and its effect on the maximum critical velocity is demonstrated with both contact models. Finally, application to pharmaceutical powder composed of carrier (coarse) and active pharmaceutical ingredient (API) (fine) particles in a shaken capsule prove this to be an example of vulnerability to the phenomenon of fine particle ejection and to significantly benefit from the thick wall modification.